2013
DOI: 10.4238/2013.october.7.7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of UV-B-induced microRNAs in wheat

et al.

Abstract: ABSTRACT. MicroRNAs (miRNAs) play critical roles in posttranscriptional gene regulation and act as important endogenous regulators to various stressors. Ultraviolet-B (UV-B) radiation is a major factor influencing crop growth and development. In this study, we isolated a novel wheat miRNA, named Tae-miR6000, and confirmed its expression diversity after UV-B treatments. Additionally, using the Northern blotting technique, we found that six miRNAs were highly responsive to UV-B stress in wheat. Of these six miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 34 publications
2
47
0
Order By: Relevance
“…The overproduction of ROS in living organisms under stressful conditions is potentially toxic because ROS may attack biomolecules such as lipids, proteins, and DNA, as well as some small molecules. As a result, oxidative damage or even organism death may occur (Wang et al, 2013). To cope with ROS toxicity, plant cells use numerous highly efficient antioxidant systems comprised of enzymatic and non-enzymatic constituents (Carletti et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The overproduction of ROS in living organisms under stressful conditions is potentially toxic because ROS may attack biomolecules such as lipids, proteins, and DNA, as well as some small molecules. As a result, oxidative damage or even organism death may occur (Wang et al, 2013). To cope with ROS toxicity, plant cells use numerous highly efficient antioxidant systems comprised of enzymatic and non-enzymatic constituents (Carletti et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…miR168 plays a pivotal role as it regulates the expression of AGO1, a mechanism through which all microRNAs can down-regulate their targets Gazzani et al, 2009). In addition, miR168 is reportedly involved in the regulation of plant growth, fruit development, and response to different stresses, such as UV-B and aluminum, and is also up-regulated during viral infection in plants, during which it is ubiquitous in plant-virus interactions (Várallyay et al, 2010;Lima et al, 2011;Wang et al, 2013;Xian et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, we performed a literature search to investigate what miRNAs respond to H 2 O 2 or UV-B radiation as well as ionizing radiation (Table 1); however, only a few articles could be identified. Expression of the miR156 and miR164 families was found to respond to UV-B radiation and carbon ions (Jia et al, 2009;Zhang et al, 2011a;Casati, 2013;Wang et al, 2013), while expression of the miR169 family was affected by UV-B radiation and H 2 O 2 (Zhou et al, 2007;Jia et al, 2009;Li et al, 2011). Previously, we demonstrated that genome-wide transcriptional changes in Arabidopsis seedlings subjected to gamma irradiation were most clear at 6 h and then decreased until 48 h (Kim et al, 2013b).…”
Section: Results and Discussion Microrna Microarray And Gene Chip Expmentioning
confidence: 99%
“…Distinctive cis-elements in the 5'-upstream sequences or putative promoter regions of UV-B-responsive miRNA genes have been identified in A. thaliana, Populus tremula, and Triticum aestivum (Zhou et al, 2007;Jia et al, 2009;Wang et al, 2013). Many of the UV-Bresponsive cis-elements including G-box, I-box core, ARE, and MBS were frequently found in the putative promoter regions of gamma-ray-responsive miRNA genes (Table 3).…”
Section: Prediction Of Cis-elements In the Upstream Regions Of Gamma-mentioning
confidence: 99%
See 1 more Smart Citation